Assessing an artificial wetland in Putrajaya, Malaysia, as an alternate habitat for waterbirds - Rajpar, Muhammad Nawaz; Hussin, Mohamed Zakaria (The Waterbird Society, 2013)
Detailed information on bird populations and wetland habitats is highly important for future conservation and management activities. More than 50% of natural wetland habitats have been lost or degraded due to human intervention, which has negatively affected wetland-dependent bird populations. In this study, the density, diversity and feeding guilds of various bird species in an artificial wetland habitat were examined using a distance sampling point count technique. A total of 20,010 individuals of 102 species representing 40 families were detected from March 2009 to June 2010. In all, 64 species were counted with 72.5% of 14,520 individuals residents, 22 species were counted with 26.4% of 5,290 individuals resident-migrants, 13 species were counted with 1.0% of 196 individuals migrants and three species were counted with 0.1% of four individuals counted vagrants. Resident birds were present at the highest density and vagrants at the lowest. The most dominant migrant, resident and resident-migrant species were the Oriental Reed Warbler (Acrocephalus orientalis) (0.37 ±0.10 birds ha-1), Rock Pigeon ( Columba livia) (3.91 + 0.97 birds ha-1) and Purple Heron (Ardea purpurea) (1.55 ± 0.93 birds ha-1), respectively. The community structure of resident birds was the most diverse and rich compared to migrants, resident-migrants and vagrants. Frugivore/insectivore (1.04 ± 0.20 birds ha-1) was the most dominant feeding guild for migrants, nectarivore/insectivore (0.64 ± 0.04 birds ha-1) for residents and omnivore (0.28 ± 0.03 birds ha-1) for resident-migrants. The findings of this research indicate that artificial wetlands can provide an alternative habitat for the foraging and breeding activities of different bird assemblages.